Mercury and Parkinson’s Disease: Promising Leads, but Research Is Needed - E. Fuller Torrey; Wendy Simmons (Parkinson's Disease)
Environmental toxicants are thought to play a major role in the pathogenesis of Parkinson’s disease. In reviewing the literature on heavy metals known to be toxicants, we noted several recent studies on mercury suggesting a possible role in the etiology of some cases of this disease. We therefore undertook a review of this association, focusing especially on peer-reviewed articles to avoid the bias inherent in much of the literature regarding mercury. For most people, our contemporary exposure to mercury comes from dental amalgam tooth restorations and from eating fish contaminated with mercury. In both cases, mercury is known to get into the brain in utero and at all ages. It remains in the brain for many years and is known to produce permanent neuropsychological deficits. Mercury toxicity can produce tremors and other Parkinsonian clinical symptoms. It can also produce neurochemical and neuropathological changes similar to those found in Parkinson’s disease, including the loss of dopamine neurons, degeneration of tubulin and axons, dysfunction of mitochondria, and the aggregation of alpha-synuclein. Relatively few studies have assessed mercury in parkinsonian patients, but almost all reported a statistically significant association. Published studies suggest some promising leads in the relationship between mercury exposure and Parkinson’s disease. However, studies of patients are relatively few, and the need for research is clear. A search of Parkinsonian research studies currently funded by the US National Institutes of Health, Parkinson’s Foundation, and the Michael J Fox Foundation yielded no studies on mercury. We believe such studies should be supported.